ASYMPTOTICALLY OPTIMAL QUADRATURE FORMULAE IN CERTAIN SOBOLEV CLASSES (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2015)
We construct sequences of asymptotically optimal quadrature formulae in the Sobolev classes $W^3_p ( 1 ≤ p ≤ ∞)$ , and $W^4_1$. Sharp error bounds for these quadrature formulae are given.